Where the tallest mangroves are. Issue 1 (January 2019) - Friess, Daniel
Mangrove canopy heights vary around the world in response to rain, storms and human activities, suggests a global analysis of mangrove canopy height. How tall the trees are matters for estimating global mangrove carbon storage.